Expert Witnessing in the Asylum Economy. Issue 1 (28th January 2022) - Moodie, Ellen
Abstract: Homeland Security lawyers routinely ask experts in immigration court cases about compensation for their labor. The suggestion is that if money has been exchanged, perhaps their opinions have been bought. Meanwhile, pro bono offerings can be seen as "activism"—motivated beyond the court‐framed "truth." Even as I offer many declarations pro bono, I have come to recognize, uneasily, my role in an extended network of coyote types who convey people to safety. In this contribution, I delve into personal discomfort as I consider the expert's position in the political economy of migrant movement today.